Peran Strategis Konsultan Pajak dalam Pengambilan Keputusan Bisnis pada Perusahaan Berbasis Teknologi: Studi Literatur - Bagus Risanto; Dwi Irma Febriani; Iqnatia Septiany Karina (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2026)
The development of the digital economy has led to increasing complexity in tax management for technology-based companies. Various digital business activities, such as cross-border transactions, the utilization of intangible assets, and evolving tax regulations, require companies to adopt appropriate tax strategies. This study aims to analyze the strategic role of tax consultants in supporting business decision-making within technology-based firms. The research employs a qualitative approach using a literature review method, examining various scientific journals, books, tax regulations, and relevant professional publications. The findings indicate that tax consultants no longer function solely as compliance supporters but have evolved into strategic partners for companies in tax planning, the utilization of fiscal incentives, tax risk mitigation, digital transaction management, and investment and business expansion decision-making. This role contributes to improved financial efficiency and reduced tax-related legal risks. This study emphasizes that the involvement of tax consultants from the business planning stage can enhance the quality of managerial decision-making in technology-based companies.